Life Expectancy in Marine Mammals Is Unrelated to Telomere Length but Is Associated With Body Size - Buddhachat, Kittisak; Brown, Janine L.; Kaewkool, Manthanee; Poommouang, Anocha; Kaewmong, Patcharaporn; Kittiwattanawong, Kongkiat; Nganvongpanit, Korakot (Frontiers in Genetics, 2021)
Marine mammals vary greatly in size and lifespans across species. This study determined whether measures of adult body weight, length and relative telomere length were related to lifespan. Skin tissue samples (n=338) were obtained from 23 marine mammal species, including four Mysticeti, 19 Odontoceti and one dugong species, and the DNA extracted to measure telomere length using real-time PCR. Life span, adult body weight, and adult body length of each species were retrieved from existing databases. The phylogenetic signal analysis revealed that body length might be a significant factor for shaping evolutionary processes of cetacean species through time, especially for genus Balaenoptera that have an enormous size. Further, our study found correlations between lifespan and adult body weight (R2= 0.6465, p<0.001) and adult body length (R2=0.6142, p=<0.001), but no correlations with relative telomere length (R2=-0.0476, p=0.9826). While data support our hypothesis that larger marine mammals live longer, relative telomere length is not a good indicator of species longevity.